FUNDAMENTAL PHENOMENA IN WOOD RFV DRYING WITH 50-Ohm AMPLIFIER TECHNOLOGY - Anastasios Koumoutsakos (Maderas: Ciencia y Tecnología, 2002)
Radio frequency/vacuum drying (RFV) experiments were conducted on thick (200-250 mm) softwoods by using a 50-Ohm amplifier as the radio frequency (RF) source. The power densities selected were low to ensure highest quality of the final product and that no internal checking will occur. The effect of dryer pressures and power densities on the drying kinetics and product quality was examined for two different wood species. A number of experimental observations and drying characteristics are analyzed and discussed in detail. The concept of the identity drying card is applied and useful information concerning the drying mechanisms and the relevant phase transitions is obtained